Modern E-technologies and Academic Staff Job Productivity in Nigerian Colleges of Education - Cletus Akpo Atah; I. M. Idike; Rosemary Young Godwin; Kolo Isaac; Donatus Ugbadu Ititim; Ogbiji Michael Okpe; Ochui Moses Orim (Richtmann Publishing, 2023)
The purpose of this study was to ascertain the influence modern e-technologies on academic staff productivity in Nigerian colleges of education. To achieve the study's goal, one research question was posed, and one hypothesis was developed to direct the investigation. The study utilized a survey-based design. The study's population consists of eighty-one (81) business education academic staff members, who were all participating in the research due to the population's manageable size. For data collection, an 11-item questionnaire titled